ANALISIS DAMPAK PENGGUNAAN HANDPHONE TERHADAP MINAT BELAJAR SISWA KELAS V SDN 12 ENGKURAI - Crishandova, Egi; Waridah, Waridah; Anggorowati, Kurnia Dyah (STKIP Melawi, 2024)
Abstract: The background of this research is based on the impact of using cellphones on the learning interest of class V students at Engkurai 12 State Elementary School. The purpose of this research is to determine the impact of cellphones on the interest in learning of class V students at 12 Engkurai Elementary School, North Pinoh District. This type of research uses qualitative descriptive research, while the data collection techniques used are interviews, observation and documentation directly with informants in the field to obtain the required data. Data analysis in this research uses the Miles and Huberman flow model data analysis technique, namely data reduction, data presentation, and drawing conclusions or verification to determine the impact of cellphone use on students' interest in learning. The results of the research are the negative impact of using cellphones on the interest in learning of fifth grade students at the Engkurai 12 Elementary School, North Pinoh District, including: students experiencing a decrease in interest in learning, lack of student attention to the lessons given, tantrums, decreased social abilities in students, brain growth in students become disturbed, and students' ability to be independent decreases. This impact is caused by children using cellphones too often at home without being controlled by their parents and children who are addicted to using cellphones feel that cellphones are the most interesting thing more than playing with people around them or their peers. Based on the results of the research conductedy researchers, the conclusion of this study shows that the use of handphone has a significant impact on the learning interest of class V students at the 12 Engkurai state Elementary School. The results of data analysis show that there is a negative correlation between the intensity of handphones use and studentsâ€™ interest in learning, the higher the use of handphones, the lower the studentâ€™s interest in learningKeywords: Use of Gadgets, Interest in Student Learning.Â Abstrak: Latar belakang penelitian ini didasarkan pada dampak penggunaan handphone terhadap minat belajar siswa kelas V Sekolah Dasar Negeri 12 Engkurai. Tujuan penelitian ini adalah untuk mengetahui dampak handphone terhadap minat belajar siswa kelas V Sekolah Dasar Negeri 12 Engkurai Kecamatan Pinoh Utara. Jenis penelitian ini menggunakan penelitian deskriptif kualitatif, sedangkan teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi secara langsung dengan informan dilapangan untuk mendapatkan data yang dibutuhkan. Analisis data dalam penelitian ini menggunakan teknik analisis data model alir Miles dan Huberman yaitu reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi guna mengetahuai dampak penggunaan handphone terhadap minat belajar siswa. Hasil dari penelitian adalah dampak negatif penggunaan handphone terhadap minat belajar siswa kelas V Sekolah Dasar Negeri 12 Engkurai Kecamatan Pinoh Utara antara lain: siswa mengalami penurunan minat belajar, kurangnya perhatian siswa terhadap pelajaran yang diberikan, tantrum, menurunnya kemampuan sosial pada siswa, pertumbuhan otak pada siswa menjadi terganggu, dan menurunnya kemampuan siswa untuk mandiri. Dampak tersebut disebabkan karena anak terlalu sering menggunakan handphone di rumah tanpa dikontrol oleh orang tua dan anak yang sudah kecanduan menggunakan handphone merasa handphone adalah hal yang paling menarik melebihi bermain dengan orang-orang sekitar atau teman sebayanya. Berdasarkan hasil dari penelitian yang dilakukan oleh peneliti maka kesimpulan dari penelitian ini menunjukkan bahwa penggunaan handphone memiliki dampak yang signifikan terhadap minat belajar siswa kelas V Sekolah Dasar Negeri 12 Engkurai. Hasil analisis data meunjukkan bahwa adanya korelasi negatif antara intensitas penggunaan handphone dengan minat belajar siswa. Semakin tinggi penggunaan hanphone, semakin rendah minat belajar siswa.Kata Kunci : Handphone, Minat Belajar Siswa, Sekolah Dasar